2019
DOI: 10.3889/oamjms.2019.426
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin’s Effect оn COX-2 аnd IL-10 Serum in Preeclampsia’s Patient Undergo Sectio Caesarea with Spinal Anesthesia

Abstract: BACKGROUND: Curcumin is a major component in curcuminoid which acts as an anti-inflammatory agent. Curcumin affects several biological markers that are thought to play a role in the pathogenesis of preeclampsia such as IL-10 and COX-2, resulting in an improvement in pregnant women with preeclampsia. AIM: To see the effect of perioperative curcumin administration on IL-10 and COX-2 in preeclamptic patients undergoing caesarean section under spinal anaesthesia. METHODS: This study was a double-blind,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Recently, a double-blind randomized clinical trial involving 47 pregnant women with preeclampsia was conducted to evaluate the possible effect of curcumin on the expression of COX-2 and IL-10, thought to have a role in the pathogenesis of PE. The enrolled patients were randomized to receive either curcumin 100 mg/d ( n = 23) or placebo ( n = 24) [ 54 ]. The authors analyzed the circulating levels of IL-10 and COX-2, at T0, 90 min after curcumin ingestion, and 12 h after delivery.…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a double-blind randomized clinical trial involving 47 pregnant women with preeclampsia was conducted to evaluate the possible effect of curcumin on the expression of COX-2 and IL-10, thought to have a role in the pathogenesis of PE. The enrolled patients were randomized to receive either curcumin 100 mg/d ( n = 23) or placebo ( n = 24) [ 54 ]. The authors analyzed the circulating levels of IL-10 and COX-2, at T0, 90 min after curcumin ingestion, and 12 h after delivery.…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 99%
“…Results showed that curcumin did not modify the expression of the analyzed molecules at any tested time. The authors hypothesized that the absence of effect might be due to the low dose of curcumin, taking into account that in non-pregnant subjects doses can reach more than 1 g/day [ 54 ].…”
Section: Role Of Curcumin In Pregnancymentioning
confidence: 99%
“…-no significant differences in level of markers in serum of patients. [91] Epigallocatechin gallate -double-blind, randomized, placebo-controlled clinical trial, -pregnant women with severe pre-eclampsia (n = 304 patients), -dose of epigallocatechin gallate:…”
Section: Curcuminmentioning
confidence: 99%
“…Fadinie et al [ 91 ] drew attention to the anti-inflammatory properties of curcumin, which can inhibit the activation of NF-κβ and may influence the activity and concentrations of COX-2 and IL-10, involved in the pathogenesis of preeclampsia. In order to verify this assumption, Fadinie et al [ 91 ] carried out a double-blinded, randomized clinical trial with pregnant women with preeclampsia ( n = 47). Patients received medicinal products containing 100 mg of curcumin once daily ( n = 23).…”
Section: Polyphenolic Compounds In Clinical Trials and Case-contromentioning
confidence: 99%
See 1 more Smart Citation